Eruption Disturbance in Children Receiving Bisphosphonates: Two Case Reports - Tatsuya Akitomo; Yuko Iwamoto; Mariko Kametani; Ami Kaneki; Taku Nishimura; Chieko Mitsuhata; Ryota Nomura (Pharmaceuticals)
Background: Bisphosphonates used for the treatment of osteoporosis, hypercalcemia, or heterotopic calcifications can cause serious adverse dental events such as osteonecrosis of the maxillary and mandibular bones. However, the effects in childhood remain scarcely explored. Case Presentations: We encountered two children who had started bisphosphonate therapy before completion of the primary dentition. No systemic disease causing congenital delayed tooth eruption was diagnosed. Although the children’s height and weight increased with age, their tooth eruption was significantly delayed compared with the mean. The primary teeth gradually erupted in the follow-up period; however, some teeth did not completely erupt and needed to be extracted to allow for permanent tooth eruption. Conclusions: We report a case of children with early use of bisphosphonates and eruption disturbance, highlighting the need for further investigation into the relationship between these factors.